Subjects with substituted hypothyroidism oxidize more lipids and carbohydrates during exercise - Jean-Frederic Brun; Stephanie Metrat; Jean-Marie Nguyen; Marlene Richou; Fatiha M'Rabta; Orianne Villard; Francois Bughin; Christine Fedou; Ariane Sultan; Antoine Avignon; Jacques Mercier2; Eric Raynaud De Mauverger (Annals of Musculoskeletal Medicine - Peertechz Publications, 2018)
Subjects with hypothyroidism substituted with levothyroxine (HS) are known to be poor responders to weight reducing strategies. Since muscle energy metabolism is regulated by thyroid hormones we compared the oxidation of fat and carbohydrates (CHO) during exercise in HS versus controls. We compared 52 patients (48 women, 4 men, age 49 t years, levothyroxine dose 25-250 micrograms / day) to a control group of 2081 patients matched for sex, age, BMI and percentage of fat during an exercise calorimetry with 4 submaximal 6 minutes steps. At the same power intensity HS on the average oxidize more fat (p = 0.009) and use more oxygen (p = 0.00019). Lipid oxidation culminates at the same power intensity(39,4±2,4 vs 38,6±0,3 watts) but its maximal oxidation rate is significantly higher in the HS group (10.32±0.47 vs. 9, 06±0.10 mg / min / kg muscle p = 0.02) and carbohydrate oxidation during the final level (1866.6 ± 77.3 vs1705.45 ± 11.5 mg / min p = 0.029 ). The maximal lipid oxidation rate is correlated with the dose of levothyroxine (r = 0.331, p <0.05).HS patients exhibit an overall increase of energy expenditure during exercise, oxidizing more lipids at mild to moderate intensities and more CHO at high intensities. This latter mechanism could result into an orexigenic effect of physical activity contributing to resistance to weight loss.